Experience of physicians during COVID-19 in a developing country: a qualitative study of Pakistan - Wajiha Haq; Fareyha Said; Sidrah Batool; Hafiz Muhammad Awais (Journal of Infection in Developing Countries)
COVID-19 spread rapidly and jeopardised the physicians with not only treatment but also with limited resources and new working style. This study aimed to investigate the experience of physicians in Pakistan as frontline workers for the treatment of COVID-19 patients. The study employed a qualitative design and used Haas's adaptation of Colaizzi method for analysis. The respondents for the interview were selected based on purposive sampling and only those physicians were contacted who were treating COVID-19 patients in Lahore, Pakistan. The results of the study revealed many challenges faced by Pakistani physicians which included physical and psychological stress due to the treatment of COVID-19 patients. Moreover, infrastructural flaws have added in the vulnerabilities of the physicians. In developing countries, the fight is much harder for physicians as evidenced by their first-hand experience. The policymakers in developing countries especially in Pakistan can direct policies facilitating physicians to reduce their physical and psychological stress as well as increasing resources for the treatment of COVID-19 patients.